Work-Life Balance In Mobile Working Era: A Bibliometric Analysis - Maulidya Alfi Anita Zain; Madziatul Churiyah (CV. Syntax Corporation Indonesia, 2022)
Information and communication technology (ICT) has an important role in economic development throughout the world. One of the choices of new methods that involve technology to complete a job remotely is mobile working. The application of mobile working provides many benefits for workers and companies. One of the benefits of implementing mobile working is improving work-life balance. Work-life balance is an individual's ability, regardless of gender, to balance work and family obligations. Research related to work-life balance in the era of mobile working is still lacking, especially in the Asian region. In addition, the main keyword that dominates the work-life balance is still the work environment. In the mobile working era, work-life balance was investigated using bibliometric methods to provide an appropriate reference for further research. Objective this research aims to provide a comprehensive bibliometric literature study on work-life balance in the mobile working era. The articles in this study were obtained from the Scopus database, a total of 47 articles related to work-life balance in the mobile working era in 2020-2022. Researchers use VOSviewer software to help conduct co-authorship, co-occurrence, and citation analysis.